TRANSLATION OF ENGLISH-INDONESIAN NOUN PHRASES: IDENTIFICATION OF LOSS, ADDITION AND SKEWING - I Gusti Agung Sri Rwa Jayantini; I Komang Sulatra; Donatus Darso; Ni Komang Arie Suwastini (Sanata Dharma University, 2021)
This study focuses on the analysis of how information may be lost, added, and skewed in the English-Indonesian translation of noun phrases in the novel The Valley of Fear. This study utilized descriptive qualitative method through note-taking technique. Nida’s principles of translation were applied to investigate how these three principles occur. The results showed that loss, addition, and skewing were found with several classifications, namely (1) omission of adjectives and indefinite quantifiers as well as different grammatical points of view for loss of information, (2) different linguistic and cultural aspects for addition of information, and (3) deviation of meaning and the choice of closest natural equivalence for skewing of information. Of the 507 cases found, addition of information occurs on the highest percentage, i.e. 54,81% (278 data), loss of information takes 41,42% (210 data) and skewing of information takes the lowest percentage, i.e. 3,74% (19 data). These findings indicate that actually loss, addition and skewing take place in translation of noun phases from English into Indonesian for the sake of finding naturalness without neglecting the accuracy of transferring meaning.